2013
DOI: 10.4103/0972-124x.119286
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease and type I diabetes mellitus: Associations with glycemic control and complications

Abstract: Objective:The aim of the study was to evaluate periodontal health status in patients diagnosed with type 1 diabetes mellitus (DM1) and to establish a correlation between metabolic control and periodontal health status.Materials and Methods:Periodontal health parameters namely plaque index (PI), gingival index (GI), probing pocket depth (PPD) and clinical attachment loss (CAL) were recorded in 28 patients diagnosed with type 1 diabetes mellitus (DM1) and 20 healthy controls. Diabetes history was recorded based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 15 publications
0
32
0
6
Order By: Relevance
“…10,11 ). In a classic cross-sectional study, type 1 diabetes has been associated with a fivefold increased prevalence of periodontitis in teenagers 12 and with greater bleeding index, probing pocket depth and clinical attachment level 13,14 . Today, chronic periodontitis has been identified as the sixth complication of diabetes alongside retinopathy, nephropathy, neuropathy, macrovascular disease and poor wound healing 15 .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 ). In a classic cross-sectional study, type 1 diabetes has been associated with a fivefold increased prevalence of periodontitis in teenagers 12 and with greater bleeding index, probing pocket depth and clinical attachment level 13,14 . Today, chronic periodontitis has been identified as the sixth complication of diabetes alongside retinopathy, nephropathy, neuropathy, macrovascular disease and poor wound healing 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Attention to the importance of disease prevention has increased due to the association of periodontal disease with systemic diseases including cardiovascular disease and diabetes, as well as tooth loss 1,2 . However, a study in 2013 found that Korean males older than 40 years of age had a 37.9% prevalence of periodontal disease, and one of every two males older than 50 years and at least one-third of females of the same age group had periodontal disease 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Causes for periodontal diseases are known to be various factors, dental occurrence of periodontal disease is higher and accelerates resorption of alveolar bone, and inadequate control of blood sugar level was related to the severity of periodontal diseases [13][14][15][16][17][18][19][20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%